Stacked traits conferring multiple resistance to imazamox and glufosinate in soft wheat - Domínguez - Mendez, Rafael (2020)
Convencional crossing of soft cultivars resistant to imazamox and glufosinate resulted in two (Rados and Helter) lines resistant to both herbicides. Stacked traits dual herbicide in these lines, compared with a susceptible (s) cultivar, were characterized.